Usability Testing Pada Website SMK Negeri 1 Suak Tapeh Menggunakan System Usability Scale (SUS) - Robby Arief Lesmana; Ahmad Mutatkin Bakti (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Website is a technology-based site that allows users to get information from surfing (browsing). The website is currently being used in various types of institutions, including educational institutions such as SMK Negeri 1 Suak Tapeh. Given the importance of the website as a medium of information, it is necessary to evaluate whether the information provided and the existing website have a useful value for users or not. The evaluation process is carried out using the System Usability Scale (SUS) with ten statements and ten respondents. The final result of the website assessment of SMK Negeri 1 Suak Tapeh got a score of 64.9. From the results of the assessment, it is in accordance with the provisions of the System Usability Scale that the website of SMK Negeri 1 Suak Tapeh has an adjective rating of good with a marginal high category. While the grade scale belongs to group D and the level of acceptance (acceptability) is acceptable.